Targeting phospholipase D with small-molecule inhibitors as a potential therapeutic approach for cancer metastasis - Su, Wenjuan (2009)
Phospholipase D (PLD)1 and PLD2, the classic mammalian members of the PLD uperfamily, have been linked over the past three decades to immune cell function and to cell biological processes required by cancer cells for metastasis. However, owing to the lack of effective small-molecule inhibitors, it has not been possible to validate these roles for the PLDs and to explore the possible utility of acute and chronic PLD inhibition in vivo. The first such inhibitors have recently been described and demonstrated to block neutrophil chemotaxis and invasion by breast cancer cells in culture, increasing the prospects for a new class of therapeutics for autoimmune disorders and several types of metastatic cancer.